Unwanted Hormonal and Metabolic Effects of Postoperative Adjuvant Mitotane Treatment for Adrenocortical Cancer - Basile, Vittoria (Cancers (Basel), 2020)
SIMPLE SUMMARY: Mitotane is the only drug approved for treatment of adrenocortical cancer. Although mitotane is a derivative of the pesticide dichlorodiphenyltrichloroethane (DDT), limited data are available on its toxicity. Herein, we reported on the type and frequency of mitotane adverse events and on supportive therapies used to deal with toxicity in 74 mitotane-treated patients. Beyond the expected glucocorticoid insufficiency, a significant number of patients had a deficit of mineralocorticoid hormones, hypothyroid state and impaired testicular function, while fertile women frequently developed ovarian cysts during mitotane treatment. Multiple hormone replacement therapies were needed in >30% of patients. Statins were used in 50% of patients for significant hypercholesterolemia. Supportive therapies were able to revert the biochemical alterations, although higher doses were frequently used due to pharmacokinetic interactions with mitotane. Our study underlines the need of a careful and global approach to manage mitotane toxicity, to make adjuvant therapy safer and easier for patients. ABSTRACT: Mitotane is widely used for the treatment of adrenocortical cancer (ACC), although the drug-related toxicity complicates its use. The aim of this study is to assess comprehensively the different endocrine and metabolic unwanted effects of the drug, and to provide data on the supportive therapies. We retrospectively analyzed 74 ACC patients adjuvantly treated with mitotane for ≥12 months. During the treatment period (40 months, 12–195), 32.4% of patients needed replacement therapy for mineralocorticoid deficit, 36.2% for hypothyroidism and 34.3% for male hypogonadism. In fertile women, hypogonadism was uncommon, while 65.4% of women developed ovarian cysts. Although no significant change in low-density lipoprotein (LDL) was observed, statins were started in 50% of patients for a significant increase in total cholesterol and triglycerides. Dyslipidemia occurred early, after a median time of 6 months from mitotane start. Conversely, testosterone replacement was usually started after >2 years. In many cases, ranging from 29.4% to 50% according to the side effect, toxicity occurred well before the achievement of the target mitotane concentrations. Supportive therapies were able to revert the biochemical alterations induced by mitotane, although higher doses were needed for a likely pharmacokinetic interaction of exogenous steroids and statins with mitotane. In conclusion, adjuvant mitotane therapy is associated with a spectrum of unwanted effects encompassing the function of different endocrine glands and requires a careful clinical and biochemical assessment associated with the therapeutic drug monitoring.